2015
DOI: 10.1111/mve.12150
|View full text |Cite
|
Sign up to set email alerts
|

The dying of the light: crepuscular activity in Culicoides and impact on light trap efficacy at temperate latitudes

Abstract: The light trap is the tool of choice for conducting large-scale Culicoides (Diptera: Ceratopogonidae) vector surveillance programmes. Its efficacy is in doubt, however. To assess this, hourly changes in Culicoides activity over the 24-h diel were determined comparatively by way of light trapping and aerial sweeping, and correlated against light intensity. In the Netherlands, sweeping around cattle at pasture revealed that, in early summer, Culicoides are active throughout the diel, and that their abundance pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Midges are least active during the brightest hours of the day (Meiswinkel & Elbers, 2016), thus marking the period when horses can be aired and pastured most safely. However, during the day, frequent cloud cover and the associated drop in light intensity, will trigger midge activity, with the result that horses at pasture will nearly always need protective blankets, a hoodie, and leg bandages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Midges are least active during the brightest hours of the day (Meiswinkel & Elbers, 2016), thus marking the period when horses can be aired and pastured most safely. However, during the day, frequent cloud cover and the associated drop in light intensity, will trigger midge activity, with the result that horses at pasture will nearly always need protective blankets, a hoodie, and leg bandages.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, this dress regimen should reduce Culicoides attacks on the horse, but to what extent remains to be tested experimentally. At more northerly latitudes, midges are most active during low-light conditions at dusk and dawn (Service, 1969;Gerry et al, 2008;Meiswinkel & Elbers, 2016), which thus form those periods of the day when the horse is most at risk and in need of protection. However, the absence of housing for approximately half of the horse population of The Netherlands, would render it impossible to exploit this 'dusk-and-dawn' bimodality to circumvent vector attacks.…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands, efficacy of light traps was compared with aerial sweeping, and correlated against light intensity (Meiswinkel and Elbers, 2016). C. chiopterus and C. obsoletus/C.…”
Section: Hours Of Attack and Dispersalmentioning
confidence: 99%
“…Several publications have highlighted the discrepancy between Culicoides abundance data recorded with UV light traps and those data collected with host-baited traps [46][47][48], indicating that abundance data based on UV light traps could not used as a direct estimation of biting rate. However, Viennet et al [49,50] showed that UV light trap collections were linearly correlated to attack rates on animals for several Culicoides species.…”
Section: Sampling Methods For Biting Midges Introductionmentioning
confidence: 99%